Blueberry-added black tea: Effects of infusion temperature, drying method, fruit concentration on the iron-polyphenol complex formation, polyphenols profile, antioxidant activity, and sensory properties. (1st June 2023) - Dasdemir, Yesim; Findik, Bahar Tuba; Yildiz, Hilal; Birisci, Esma
Graphical abstract: Highlights: By combining blueberries and black tea, a novel product was created and characterized. The blueberry addition inhibited the iron-polyphenol complex formation by 97%. The mixture of freeze-dried blueberries (50%) and black tea (50%) was the best candidate, considering the consumer acceptance and bioactive parameters. Abstract: Herein, a food-to-food fortification with blueberries and black tea was performed for people suffering from iron deficiency, creating a new functional product with high consumer acceptance. Black tea was mixed with varying concentrations of sun-dried or freeze-dried blueberries and infused at different temperatures. Spectrophotometric analysis revealed that the addition of blueberries to black tea inhibited the formation of the iron-polyphenol complex by up to 97 % ( p <.001). Using β-carotene bleaching and 2, 2-diphenyl-1-picrylhydrazyl assays, 50 % freeze-dried blueberry and 50 % black tea (FDFBT50 ) was determined to be the sample with the highest antioxidant activity (p <.001).The polyphenol profiles were investigated by high-performance liquid chromatography. Principal component analysis (PCA) was performed to categorize the tea samples. The findings demonstrated that the FDFBT50 sample was the best candidate among the samples, considering both the consumer acceptance and the bioactive parameters that showed statistically significant differences.